Republic of Congo : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Congo. (IMF Staff Country Reports; Country Report ;, 2021)
The COVID-19 pandemic and oil price shocks have taken a deep toll on the Congolese economy, weighing on incomes and inequality. Debt sustainability challenges precluded Fund financial assistance during the pandemic, and the Extended Credit Facility (ECF) arrangement, approved in 2019, expired in April 2021 without having completed the first review. Recently, debt sustainability has been restored owing to the authorities' debt restructuring strategy and current and projected higher oil prices. However, the risk of debt distress remains high given liquidity risks and vulnerabilities to negative oil price shocks. The authorities are actively negotiating the resolution of pending external arrears. Until this process is concluded and the negotiations with two external creditors are finalized, debt is classified as being 'in distress.'